Biogenesis, characterization, and applications of Spirulina selenium nanoparticles - Asmaa S. Yassein; Rokaia B. Elamary; Eman A. Alwaleed (Microbial Cell Factories)
Abstract Background Nowadays, researchers are attracted to the phyco-synthesis of selenium nanoparticles (SeNPs) for biotechnological and medical applications as they possess many advantages such as safety, nutritional value, and easy biodegradation than gold, copper, and silver nanoparticles. Spirulina platensis is the preferred microalgae for SeNPs synthesis because it contains many compounds that increase their stability making them fit for biomedical treatments. Results The biosynthesized Spirulina platensis selenium nanoparticles (SP-SeNPs) were spherical and crystalline, with a diameter of 65 nm and a net charge of -16.7 mV. Furthermore, they were surrounded by active groups responsible for stability. The DPPH radical scavenging test assessed the antioxidant efficacy of SP-SeNPs and exposed scavenging inhibition of 79.234% at a 100 µM dosage. ABTS and H2O2 radical scavenging assay is dose-dependent recording IC50 of 50.69 and 116.18 µg/ml, respectively. The antibacterial efficacy was investigated against 13 G-negative & G-positive bacteria. The study demonstrated that SP-SeNPs had antibacterial and antibiofilm efficiencies against the tested strains with MBC of 286–333 µg/ml. The highest percentages of biofilm inhibition were recorded for Bacillus subtilis and Klebsiella pneumoniae, with ratios of 78.8 and 69.9%, respectively. The prepared SP-SeNPS efficiently suppressed the tested fungi growth with MIC (350 µg/ml) and MFCs (480–950 µg/ml). Most notably, biogenic SeNPs effectively extended the clot formation period recording 170.4 S for prothrombin time (PT) and 195.6 S for the activated partial thromboplastin time (aPTT). SP-SeNPs reduced the cell viability of breast adenocarcinoma (MCF-7) and ovarian cancer (SKOV-3) cell lines with a percentage of 17.6009% and 14.9484% at a concentration of 100 ug/ml, respectively. Moreover, SP-SeNPs could effectively alleviate the inflammation in RAW 264.7 macrophages with a reduction percentage of 8.82% in Nitric oxide concentration. Conclusion The investigation findings reveal that SP-SeNPs are a hopeful antimicrobial, anti-tumor, anticoagulant, antioxidant, and anti-inflammatory factor that can be applied in medical cures.